Assessment of phytoremediation potential of Telfaira occidentalis in the removal of Cu, Cd, and Pb in contaminated soil along River Salanta - Umar, A.B.; Dankaka, A.H.; Shah, Mohammad Manjur (Journal of Ecobiotechnology, 2020)
A Field study was carried out to examine the phytoremediation potential of some plants metals (Cd, Cu and Pb) in contaminated soils along Sallanta river, Kano. A total of one hundred and eighty (100) samples comprising of 40 (soils), 20 (effluents), and 40 (plant parts) of T. 0ccidentalis were analyzed. 0.50g of the plant tissue and 1.0g of soil sample and 50mL of the effluent sample were digested using triacid digestion method and the levels of the metals were determined by the use of atomic absorption spectrophotometry. The mean levels of the metals in plants and soils from contaminated and control sites were found to be in the sequence of Cu (27.08±3.15)> Cd (24.57±8.25)>Pb (3.00±0.52) and Cu (10.10±2.50)> Cd (2.80±0.05)>Pb (2.00±0.63) respectively. The contamination factor (CF) of all the metals in the plants were found to be in the sequence of Cd (8.35±1.53)> Cu (2.52±1.20)>Pb (1.50±0.21). The results showed that these plants can be used for the phytoextraction of the metals from contaminated soils. The values of bioaccumulation and translocation factors were also found to be more than one in almost all cases. From these results it could be recommended that the three plants investigated would be ideal for phytoremediation in multi-metal contaminated soils.